CONSTRUCTION OF AN AGROINFECTIOUS CLONE OF BEGOMOVIRUS Bean golden mosaic virus USING GIBSON ASSEMBLY - Ferro, Mayra Machado de Medeiros; Sobrinho, Roberto Ramos; Cavalcanti, Sarah Jacqueline; Oliveira, Maria Helloá Costa de; Lima, Gaus Silvestre de Andrade; Nagata, Tatsuya; Assunção, Iraildes Pereira (Caderno Verde de Agroecologia e Desenvolvimento Sustentável, 2020)
Viruses belonging to the genus Begomovirus (family Geminiviridae) infect cultivated and wild plants in tropical and subtropical regions, causing serious economic losses. The begomoviruses have circular single-strand DNA genome encapsidated into quasi-icosahedral particles, being transmitted by whitefly cryptic species into the sibling group Bemisia tabaci (Homoptera: Aleyrodidae). Therefore, this study aimed to obtain an infectious clone of BGMV, using the PCR-Gibson Assembly method. For this study, DNA-A and DNA-B genomic components of the begomovirus BGMV isolate 173 AL (GenBank accession KJ939749 for DNA-A, MH925107 for DNA-B), previously cloned into pBluescript KS+plasmid vectors were used to construct infectious clones by PCR and Gibson Assembly (GA). Aliquots of the GA reactions were used to transform Escherichia coli DH10B electrocompetent cells, and binding of the viral fragments into pJL-89 binary vector was confirmed by enzymatic digestion and sequencing. Plasmid DNA from the confirmed constructs was used for transformation of Agrobacterium tumefaciens (strain GV3101), and the infectivity of the clones was tested by agroinoculation in Phaseolus vulgaris 'cv. Pérola'. Total DNA was extracted from leaf samples (systemically infected) collected at 15- and 30-days post agroinfiltration (dpa), and used as template for viral detection using specific primers. Common bean seedlings displayed severe yellow mosaic and stunt symptoms 15 dpa with DNA-A and DNA-B of BGMV and both genomic components were detected by PCR. The approach based on PCR-GA protocol is a fast and useful tool to obtain infectious clones of a circular DNA plant virus.